Changes of mental stress biomarkers in ultramarathon - Agawa, H.; Yamada, N.; Enomoto, Y.; Suzuki, H.; Hosono, A.; Arakawa, K.; Ghadimi, R.; Miyata, M.; Maeda, K.; Shibata, K.; Tokudome, M.; Goto, C.; et al. (International Journal of Sports Medicine, 2008)
We investigated the possible influence of an exhaustive physical exercise on mental stress biomarkers (serotonin, tryptophan, and ß-endorphin) along with dopamine, noradrenalin and free fatty acids in an ultramarathon race in which 45 km was run on the first day and 90 km on the second. We obtained serum samples at 6 different time points during and after the race from 18 Japanese male runners who completed the marathon. Overall changes of serum serotonin and tryptophan concentrations were statistically significant according to ANOVA for repeated measurements (p < 0.05). Serum serotonin levels elevated rapidly on the first day with the post hoc Tukey's test. Tryptophan concentrations inversely decreased during the race, possibly because of utilization for synthesis of serotonin. Levels of ß-endorphin appeared to increase on the first and second days, but were not statistically significant. In conclusion, serum serotonin, tryptophan and ß-endorphin appeared to be used for mental stress markers in physical exercise.